MEDICINAL PROPERTIES OF GINGER (ZINGIBER OFFICINALE) - Оstоnоvа Gulnоzа Rаshidоvnа (Лучшие интеллектуальные исследования, 2024)
Abstract: This article is about the appearance and medicinal properties of the medicinal ginger plant. The root of the ginger plant is widely used in medicine.